2017
DOI: 10.1021/acs.energyfuels.7b00702
|View full text |Cite
|
Sign up to set email alerts
|

Cleat Orientation from Ground Mapping and Image Log Studies for In Situ Stress Analysis: Coal Bed Methane Exploration in South Karanpura Coalfield, India

Abstract: Conventional well logs from three wells in South Karanpura coalfield are analyzed to correlate 10 major coal seams belonging to the Barakar formation for coalbed methane (CBM) exploration. Face cleat orientations are studied for the Simana and Argada coal seams from the Sirka and Argada mines. It varies from 130 to 140°N for a total 349 face cleats observed from Simana and Argada coal seams. Cleat identification and its orientation have also been analyzed from simultaneous acoustic and resistivity (STAR) log f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…In the image log, drilling-induced fractures (DIFs) and borehole breakouts (BOs) are the indicators of the present-day stress direction (Barton et al 1998;Barton and Zoback 2002;Ali et al 2017). BOs corresponds to the Sh direction occurs due to low mud weight, is not observed in this study whereas DIFs are observed as a thin vertical pair of line at 180° apart in image log, correspond to the SH direction which occurs due to high mud weight (Bell and Gough 1979;Trautwein-Bruns et al 2010).…”
Section: Resistivity Image Analysismentioning
confidence: 53%
“…In the image log, drilling-induced fractures (DIFs) and borehole breakouts (BOs) are the indicators of the present-day stress direction (Barton et al 1998;Barton and Zoback 2002;Ali et al 2017). BOs corresponds to the Sh direction occurs due to low mud weight, is not observed in this study whereas DIFs are observed as a thin vertical pair of line at 180° apart in image log, correspond to the SH direction which occurs due to high mud weight (Bell and Gough 1979;Trautwein-Bruns et al 2010).…”
Section: Resistivity Image Analysismentioning
confidence: 53%
“…In‐situ stress has great influence on the original cleats orientation and permeability of coal reservoir, as well as hydraulic fractures of CBM wells . If the coal is considered to be homogeneous, continuous, and isotropic, the hydraulic fractures will first crack in the direction that is perpendicular to the minimum horizontal principal stress.…”
Section: Morphology Of Hydraulic Fractures and Prediction Model Of Pomentioning
confidence: 99%
“…6 The current in situ stress regime is not only one of the main parameters affecting the construction effect of hydraulic fracturing, but also an important factor affecting reservoir fluid migration and accumulation. 4,[7][8][9] Therefore, in the initial stage of CBM development in China, 10,11 using various methods to better understand in situ stress is an effective means of CBM exploration and development. 12 At present, the commonly used methods for in situ stress measurement include mechanical methods, geophysical methods, and geological methods.…”
Section: Introductionmentioning
confidence: 99%